2010
DOI: 10.1152/ajpgi.00149.2010
|View full text |Cite
|
Sign up to set email alerts
|

Colon luminal content and epithelial cell morphology are markedly modified in rats fed with a high-protein diet

Abstract: Hyperproteic diets are used in human nutrition to obtain body weight reduction. Although increased protein ingestion results in an increased transfer of proteins from the small to the large intestine, there is little information on the consequences of the use of such diets on the composition of large intestine content and on epithelial cell morphology and metabolism. Rats were fed for 15 days with either a normoproteic (NP, 14% protein) or a hyperproteic isocaloric diet (HP, 53% protein), and absorptive colono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 56 publications
6
108
3
Order By: Relevance
“…Recently, rats fed a high-protein diet (53% protein versus 14% in a normal diet) had a marked decrease of the height of the colonocyte brush-border membranes (p 5 0.0001) which coincided with a higher colonic protease activity (p 5 0.01) and an increased NH 3 content in the colonic lumen (p 5 0.0008) [55]. The relationship between the different measured parameters was not further investigated.…”
Section: Effect Of Protein Intakementioning
confidence: 99%
“…Recently, rats fed a high-protein diet (53% protein versus 14% in a normal diet) had a marked decrease of the height of the colonocyte brush-border membranes (p 5 0.0001) which coincided with a higher colonic protease activity (p 5 0.01) and an increased NH 3 content in the colonic lumen (p 5 0.0008) [55]. The relationship between the different measured parameters was not further investigated.…”
Section: Effect Of Protein Intakementioning
confidence: 99%
“…Young mammals (including infant and weaned pigs) have often been reported to exhibit gastrointestinal tract (GIT) dysfunction, including alterations intestinal morphology, the immune system, and absorption functions, when fed a high-protein diet [1][2][3][4][5]. A reduction in dietary crude protein (CP) levels can reduce diarrhea and nitrogen (N) excretion and repair digestive and immune function by enhancing the gene expression levels of digestive enzymes and amino acid (AA) transporters in young pigs [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…For weaned pigs, it has been suggested that the CP levels in their diets can be reduced by 2-3 points without affecting average daily gain (ADG) [4,6], feed efficiency, or gastrointestinal health when the diets are supplemented with AAs [7,8]. However, reductions exceeding 3 points have produced no effects on ADG, feed efficiency and the mRNA levels of digestive enzymes (including trypsinogen, chymotrypsin B, and dipeptidase-II and III) and AA transporters [2,4,[9][10][11][12][13], although these trends have not been observed in all studies [14][15][16]. These findings suggest that the reduction of dietary CP levels and supplementation with AAs may be an alternative method for decreasing N excretion and improving GIT digestive function while maintaining performance in young pigs.…”
Section: Introductionmentioning
confidence: 99%
“…15 Ammonia and BCFA may change the morphology of intestinal tissues and act as a tumor promoter in the gut. 16 Proteolyic fermentation also results in the formation of amines, which are the precursors to carcinogenic nitrosamine formation.…”
Section: Introductionmentioning
confidence: 99%